2020
DOI: 10.1128/msphere.00786-20
|View full text |Cite
|
Sign up to set email alerts
|

A Genome Epidemiological Study of SARS-CoV-2 Introduction into Japan

Abstract: After the first case of coronavirus disease 2019 (COVID-19) in Japan on 15 January 2020, multiple nationwide COVID-19 clusters were identified by the end of February. The Japanese government focused on mitigating the emerging COVID-19 clusters by conducting active nationwide epidemiological surveillance. However, an increasing number of cases continued to appear until early April 2020, many with unclear infection routes and no recent history of travel outside Japan. We aimed to evaluate the severe acute respir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 22 publications
3
30
0
Order By: Relevance
“…It is quite intriguing that D614G_KR is dominant despite the fact that comparable numbers of D614G and D614G_Q57H strains were introduced into Japan. For unknown reasons, strains other than D614G_KR have not been able to establish and propagate in Japan 21 .…”
Section: Discussionmentioning
confidence: 99%
“…It is quite intriguing that D614G_KR is dominant despite the fact that comparable numbers of D614G and D614G_Q57H strains were introduced into Japan. For unknown reasons, strains other than D614G_KR have not been able to establish and propagate in Japan 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the first wave was characterized by a local epidemic that occurred in a closed environment, namely a sports facility, which resulted in a chain of cluster-mediated infections, as described above. On the other hand, the second wave was characterized by the clade GR (20B) virus from Europe, which was prevalent in Japan since mid-March (Sekizuka et al, 2020a), with an increased number of cases with unknown routes of infection compared to the first wave. There was no commonality in age, sex, or behavior of the patients in the second wave, indicative of multiple routes of entry.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 In Japan, five laboratories (including our group) have deposited whole viral genome data in the public sequence database GISAID (https://www.gisaid.org/): a total of 9943 sequences have been deposited, and some results of national surveys have been summarized. 5,6 These studies indicated the importance of SARS-CoV-2 genome sequencing analysis for the prevention of outbreaks during the early pandemic period (March to April 2020). SARS-CoV-2 whole-genome data was generated using specimens from 198 patients with COVID-19 admitted to 13 collaborating hospitals located in the Tokyo metropolitan area.…”
Section: Introductionmentioning
confidence: 99%